Ultrasonic hemodynamic changes of superficial temporal artery graft in different angiogenesis outcomes of Moyamoya disease patients treated with combined revascularization surgery - Chen, Siyuan; Wang, Baoping; Wen, Yunyu; Wang, Zhibin; Long, Tinghan; Chen, Junda; Zhang, Guozhong; Li, Mingzhou; Zhang, Shichao; Pan, Jun; Feng, Wenfeng; Qi, Songtao; et al. (Frontiers in Neurology, 2023)
Combined bypass is commonly used in adult Moyamoya disease (MMD) for revascularization purposes. In this study we retrospectively studied a total of 54 operated hemispheres which accepted combined bypass sugery. We quantitatively measured the STA with ultrasound and recorded the blood flow, diameter, Pulsatility index (PI) and Resistance index (RI) to assess graft development at pre-operate and 1 day, 7 days, 3 months, and 6 months after surgery.All patients received both pre- and post- operative angiography evaluation. Patients were divided into either well- or poorly-angiogenesis groups according to the transdural collateral formation status on angiography at 6 months after surgery (W group or P group). Patients with matshushima grade A or B were diveded into W group. Patients with matshushima grade C were diveded into P group, indicating a poor angiogenesis development. Compared to preoperative values, the average blood flow and diameter of an STA graft at postoperation increased, PI and RI dropped. According to the Matsushima grade at 6 months after surgery, 30 hemispheres qualified as W group and 24 hemispheres as P group. Statistically significant differences were found between the two groups in diameter (p=0.010) as well as flow (p=0.017) at 3 months post-surgery. Flow also remained significantly different at 6 months after surgery (p=0.014). Based on GEE logistic regression evaluation, the patients with higher levels of flow post-operation were more likely to have poorly-compensated collateral. ROC analysis showed that increased flow of ≥69.5 ml/min (p =0.003; AUC =0.74) or a 604% (p =0.012; AUC =0.70) increase at 3 months post-surgery compared with the pre-operative value is the cut-off point which had the highest Youden's index for predicting P group. Furthermore, a diameter at 3 months post-surgery that is ≥0.75 mm (p =0.008; AUC =0.71) or 52% (p =0.021; AUC =0.68) wider than pre-operation also indicates a high risk of poor indirect collateral formation. The hemodynamic of the STA graft changed significantly after combined bypass surgery. An increased flow of more than 69.5 ml/min at 3 months was a good predictive factor for poor neoangiogenesis in MMD patients treated with combined bypass surgery.